2020
DOI: 10.3791/61710
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a User-Defined Peptide Gel for Controlled 3D Culture Models of Cancer and Disease

Abstract: There is a growing awareness that cells grown in 3D better model in vivo behavior than those grown in 2D. In this protocol, we describe a simple and tunable 3D hydrogel, suitable for culturing cells and tissue in a setting that matches their native environment. This is particularly important for researchers investigating the initiation, growth, and treatment of cancer where the interaction between cells and their local extracellular matrix is a fundamental part of the model. Moving to 3D culture can be challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The precursor and gel preparation method was followed as previously published 57 . A commercially available peptide preparation in powder form was used as the source of the octapeptide gelator (Pepceuticals UK, FEFEFKFK, Phe-Glu-Phe-Glu-Phe-Lys-Phe-Lys).…”
Section: Peptide Gel Precursor Preparationmentioning
confidence: 99%
“…The precursor and gel preparation method was followed as previously published 57 . A commercially available peptide preparation in powder form was used as the source of the octapeptide gelator (Pepceuticals UK, FEFEFKFK, Phe-Glu-Phe-Glu-Phe-Lys-Phe-Lys).…”
Section: Peptide Gel Precursor Preparationmentioning
confidence: 99%
“…Biomaterials for gel-type 3D cell culture are derived from natural and artificially modified materials [69]. Since gels allow independent control of matrix and ECM functionalization, Ashworth et al, (2020) demonstrated a self-assembling peptide gel for designing the 3D cell culture [70]. By controlling stiffness through peptide concentration and pH condition, the peptide gel was fully utilized with further experiments on culturing breast cancer.…”
Section: Gel-based Scaffoldsmentioning
confidence: 99%